(untitled) (Journal of Global Accounting, 2024)
In recent years, forensic accounting has emerged as a crucial area of interest to academics and researchers in several nations all over the world. The demand for forensic accountants evolved as a result of the failure of organizational external and internal audit systems to identify specific flaws in the managerial and administrative systems. This study examined the effect of forensic investigative techniques on asset misappropriation in Nigeria. The study used sampled listed manufacturing companies in Nigeria namely; Ozalla Plastics Enterprises Ltd, Comfort Triumphant Company Ltd, Millenium Manufacturing Ltd, Juhel Manufacturing Ltd, Jezco Oil Nigeria Ltd. Data for the study were collected through the use of the questionnaire. The technique of data analysis used in the study is the multiple linear regression technique. The software utilized the E-views statistical software version 11. The major findings of the study show that the benchmarking technique has a significant effect on asset misappropriation in manufacturing firms in Nigeria, the exception reporting technique has a significant effect on asset misappropriation in manufacturing firms in Nigeria, the risk assessment technique has no significant effect on asset misappropriation in manufacturing firms in Nigeria and data matching technique has no significant effect on asset misappropriation in manufacturing firms in Nigeria. This study recommends that firms should employ forensic accounting techniques to ensure high financial reporting quality